The Problems Of The Agricultural Extension Work In The Governorate Of Sulaimany - Mahmood, Bayan Ahmad; Layek, Tahir Mohamed (Sulaimani Journal for Pure and Applied Sciences, 2018)
The aim of the extension centers is to promote rural society, and the success of these centers depends on the efficiency and experience of its employees who represent the main pillar in the extension work. So, this research is targeted to identify the problems of extension work through the view of the agricultural extension workers in the Sulaimani governorate, then the arrangement of theinspects and items of these problems by term and determination of the relationship between these opinions and personal and functional variables in order to reduce them and to find appropriate solutions. The research population included all workers in the field of the agricultural extension in the Sulaimani governorate who were 143 respondents, out of these, 16 respondents have been excluded for measurement of the Reliability, and 25 respondents have been excluded due to the impossibility and inaccuracy to contact them for different reasons of their answers of the research questionnaire. Ultimately, (102) of the respondents have been undergone the research procedures. Data collection was carried out using a questionnaire form which consist of two parts, the first part included a set of personal and functional information’s, while the second part included the problems of the agricultural extension and then data entry and tabulation was processed statistically using the (SPSS) software(18). The results showed that; the large number of problems which may hinder the progress of the agricultural extension work in the Sulaimani governorate. These problems varied very little in average, which is indicating that most of the extension centers suffered with these problems substantially. The results of the study also showed that the field of problems (related to the agricultural extension training) came in the first rank, while the field of the problems (related to the workers) in the field of the agricultural extension came in the last rank. The results of this study explained that there is a significant correlation between the problems of the agricultural extension work and all of the following variables (level of education, work place, and exposure to resources of agricultural information), and a non-significant correlation between the (agricultural extension work problems and all of the following variables (length of service in extension work and the attitude toward the agricultural extension). In studying correlation between opinions of the workers and the set of the independent variables, it was found that the variable (educational level) is the most contributing factor in explaining the variation in the problems existed among the extension workers in the centers followed by the variable (work place) then (exposure to resources of information). Thus, the study recommended that the Ministry of Agriculture and water recourses should resolve the impediments to the agricultural extension centers through adequate budget disbursement, giving material and moral incentives for employees, increasing the number of extension staff, and providing transportations.
Keywords: Agricultural Extension Work